Effect of geometrically thin discs on precessing, thick flows: relevance to type-C QPOs. Issue 1 (9th December 2022) - Bollimpalli, D A; Fragile, P C; Kluźniak, W
ABSTRACT: Type-C quasi-periodic oscillations (QPOs) are the low-frequency QPOs most commonly observed during the hard spectral state of X-ray binary systems. The leading model for these QPOs is the Lense-Thirring precession of a hot geometrically thick accretion flow that is misaligned with respect to the black hole spin axis. However, none of the work done to date has accounted for the effects of a surrounding geometrically thin disc on this precession, as would be the case in the truncated disc picture of the hard state. To address this, we perform a set of general relativistic magnetohydrodynamics simulations of truncated discs misaligned with the spin axes of their central black holes. Our results confirm that the inner-hot flow still undergoes precession, though at a rate that is only 5 per cent of what is predicted for an isolated precessing torus. We find that the exchange of angular momentum between the outer thin and the inner thick disc causes this slow-down in the precession rate and discuss its relevance to type-C QPOs.